2021
DOI: 10.1186/s12935-021-02038-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of methylation-driven genes prognosis signature and immune microenvironment in uterus corpus endometrial cancer

Abstract: Background Uterus corpus endometrial cancer (UCEC) is the main malignant tumor in gynecology, with a high degree of heterogeneity, especially in terms of prognosis and immunotherapy efficacy. DNA methylation is one of the most important epigenetic modifications. Studying DNA methylation can help predict the prognosis of cancer patients and provide help for clinical treatment. Our research aims to discover whether abnormal DNA methylation can predict the prognosis of UCEC and reflect the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The IPS was calculated using zscores of representative genes associated with immunogenicity. The IPSs of patients with uterine corpus endometrial carcinoma (UCEC) were extracted from The Cancer Immunome Atlas (TCIA) (https://tcia.at/home) (14).…”
Section: Immune Prognostic Signature Analysismentioning
confidence: 99%
“…The IPS was calculated using zscores of representative genes associated with immunogenicity. The IPSs of patients with uterine corpus endometrial carcinoma (UCEC) were extracted from The Cancer Immunome Atlas (TCIA) (https://tcia.at/home) (14).…”
Section: Immune Prognostic Signature Analysismentioning
confidence: 99%
“…DNA methylation is a crucial epigenetic modification type participating a series of biological and pathological processes 7–11 . Aberrant DNA methylation states have been identified in numerous malignant diseases, such as breast cancer, melanoma, colorectal cancer, prostate cancer, and gastric cancer 7,12–17 .…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is a crucial epigenetic modification type participating a series of biological and pathological processes. 7 , 8 , 9 , 10 , 11 Aberrant DNA methylation states have been identified in numerous malignant diseases, such as breast cancer, melanoma, colorectal cancer, prostate cancer, and gastric cancer. 7 , 12 , 13 , 14 , 15 , 16 , 17 Meanwhile, recent studies showed that DNA methylation probes, as well as DNA methylation‐driven genes (MDGs), can be used in the prediction of prognosis, diagnosis and treatment of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…More than 50,000 women worldwide die from UCEC each year [ 2 ]. Currently, surgery combined with radiotherapy and/or chemotherapy is the standard clinical treatment option for patients with UCEC [ 3 ]. Despite the rapid development of modern medicine, the mortality rate of UCEC has continued to increase during recent years, and the prognosis of UCEC patients varies [ 4 ].…”
Section: Introductionmentioning
confidence: 99%